MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MUATAN MATEMATIKA MENGGUNAKAN MODEL LEARNING PADA SISWA KELAS V SDN SUNGAI LULUT 7 - Hidayah, Nailul; Suriansyah, Ahmad; Purwanti, Ratna (Universitas Negeri Medan, 2023)
Abstract: The point of the examination is to grasp instructor and understudy execution and further develop understudy learning results. The subjective depiction technique utilized. The sort of learning utilized is Study hall Learning (PTK). Teaching models can be differentiated based on teacher performance, with 23 points for